Explaining Russia's Output Collapse : Aggregate Sources and Regional Evidence - Dolinskaya, Irina (IMF Working Papers; Working Paper, 2001)
This paper explores sources of the output collapse in Russia during transition. A modified growth accounting framework is developed that takes into account changes in factor utilization typical of the transition process. The results indicate that declines in factor inputs and productivity were both important determinants of the output fall. The contribution of the productivity drop was critical, but smaller than previously reported. Possible causes of the reduction in productivity are assessed using data on sub-national regions within Russia. Privatization and entry of private firms are found to have generated productivity gains, while lack of exit of unviable enterprises constituted a drag on efficiency.